La actividad lúdica y su incidencia en el desarrollo socio afectivo de los niños de inicial, de la escuela Cristóbal Colón cantón “Salcedo” en el año lectivo 2013- 2014 - Chicaiza Zhindón, Alejandro René (2015)
This contribution is based on investigative poor interest that has been giving recreational activities as a fundamental part of socio affective development of children of early school Christopher Columbus, which led to a program of recreational activities that promote allow them to develop self-confidence, autonomy and personality formation. For these reasons, this program is relevant because it aims to promote the socio affective skills through recreational and educational activities that promote comprehensive education….